Creative Accounting and Implication for Dividend Payout of Companies in the Financial Sub-Sector of Nigerian Economy - Ibanichuka, Emmanuel A. L.; Ihendinihu, John U. (Richtmann Publishing, 2012)
This study examines the relationship between creative accounting (CA) and reported financial performanceof banks and insurance companies in Nigeria, and the extent CA impacts on their dividend payout ratio.Five year financial data from 2004-2008 of twenty banks and insurance companies listed on the NigerianStock Exchange (NSE) were extracted using the stratified and simple random sampling techniques. Surveydata were obtained from 386 respondents purposively selected from the chosen organizations usingresearcher-designed questionnaire validated by experts and shown to have a reliability coefficient of 0.876.Correlation and regression statistical techniques were used in analyzing the data. The results show thatcreative accounting techniques are positively associated with firm financial performance and havesignificant effect on dividend payout (DPO) with 88% of the variations in DPO being accounted for bychanges in the explanatory variables. The work concludes that the desire to showcase impressive picture ofcorporate profitability through payment of enhanced dividend often breaches professional ethics infinancial reporting The study recommends a more stringent regulatory regime with effective enforcementmechanisms to ensure compliance with accounting and auditing standards.